Life cycle-oriented low-carbon product design based on the constraint satisfaction problem - Kong, Lin; Wang, Liming; Li, Fangyi; Li, Jianfeng; Wang, Yitong; Cai, Zekang; Zhou, Jiaxuan; Guo, Jing; Wang, Geng (Energy conversion and management, 2023)
[Display omitted] •Hierarchical life cycle-oriented low-carbon product design model is constructed.•Constraint network is integrated with the design space for low-carbon design.•Hybrid optimizer is proposed to generate the low-carbon design solution. The design and development of low-carbon products have become a recent global concern due to serious greenhouse gas emissions and climate change. The design phase determines 70 % of the environmental performance of the product, which covers complex life cycle information and diversified constraints, resulting in low efficiency of life cycle modeling and difficulty in realizing design automation. Therefore, this study proposes a life cycle-oriented low-carbon design strategy based on the constraint satisfaction problem to express the association mechanism of life cycle information and constraints and efficiently generate the low-carbon design solution. Specifically, the hierarchical life cycle-oriented low-carbon design model is proposed to manage the associations of life cycle information in terms of function, structure, design feature, and machining feature. On the basis of the model, the constraint-based design space is constructed to explicitly express all the feasible design options and the constraints of the product, which can effectively support the automation of product design. Then, all design options and the constraints for product design are transformed into a constraint satisfaction problem, which can be optimized by the proposed hybrid optimizer algorithm. This algorithm supports the efficient optimization of complex products in large-scale design space, and the low-carbon design solution is effectively generated. An example of the low-carbon design of a wind turbine is given to demonstrate the capability of the suggested method, indicating that they have reduced the carbon emission of the wind turbine nearly by 19.82 % in comparison with the existing design solution, and the material acquisition and manufacturing stages generated the highest carbon emissions, accounting for 47.94 % and 56.42 %, respectively. This work effectively standardizes products’ life cycle design information and various design constraints and provides a targeted strategy for guiding designers to implement low-carbon design through the life cycle.